Application of knowledge-based expert system, Analytic Hierarchy Process and Fuzzy set Theory in Multicriteria Environmental Sensitivity Evaluation of the Urban Road Network - Klungboonkrong, Pongrid; Taylor, Michael A P (Engineering and Applied Science Research, 2013)
This paper describes the theoretical foundation and application of a decision support tool for evaluating the multicriteria Environmental Sensitivity (ES) of the Geelong road network, in Victoria, Australia. The tool is an integration of the Analytic Hierarchy Process (AHP), Fuzzy Set Theory (FST), and Knowledge-Based Expert System (KBES). In AHP synthesis phase, both principle of hierarchic composition and the fuzzy compositional evaluation methods were applied to synthesize a'' loca' priorities to drive global priorities (the Composite Environmental Sensetivity Indices (CESI)) of a'' road links. The results of the case study indicate the potential utility of the tool for assessing the environment sensitivity of urban road network at a local level, identify problem locations, and specify the possible causes of those problems. In addition, it is found that the typical AHP expresses more powerful capcbility in defferentiating links according to their combined ES characteristics than the fuzzy compositional AHP.